2015
DOI: 10.3906/bot-1403-42
|View full text |Cite
|
Sign up to set email alerts
|

Phytoremediation potential of Landoltia punctata on petroleum hydrocarbons

Abstract: doi:10.3906/bot-1403-4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
2
5
0
Order By: Relevance
“…Furthermore, our results indicate crude oil concentrations > 0.2% had a negative effect on plant growth by reducing RGR values. This is consistent with previous reports of the effect of diesel and crude oil on the RGRs of S. grossus (Al-Baldawi et al, 2015) and L. punctata (Ertekin et al, 2015) respectively. The hindering effect of oil on plant growth could be as a result of the phytotoxicity of the increased number of aromatic rings (Baek et al, 2004).…”
Section: Plant Growthsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, our results indicate crude oil concentrations > 0.2% had a negative effect on plant growth by reducing RGR values. This is consistent with previous reports of the effect of diesel and crude oil on the RGRs of S. grossus (Al-Baldawi et al, 2015) and L. punctata (Ertekin et al, 2015) respectively. The hindering effect of oil on plant growth could be as a result of the phytotoxicity of the increased number of aromatic rings (Baek et al, 2004).…”
Section: Plant Growthsupporting
confidence: 93%
“…There is an increasing number of studies that evaluate the use of plants in the petroleum contaminated freshwater areas and in these researches different plant species such as Landoltia punctata (Ertekin et al, 2015), Vetiveria zizanioides (Effendi et al, 2017) and Lemna minor (Wang et al, 2017) have been used. Azolla has a special significance between the freshwater plants used in phytoremediation.…”
Section: Introductionmentioning
confidence: 99%
“…Higher root metal concentrations and lower shoot metal concentrations at higher dose indicate restriction of Cd from the root to aerial parts via xylem sap flow. The present work, as well as Ertekin et al (2015) on Landoltia punctata and Torbati (2015) on Lemna minor, indicated the usefulness of aquatic plants for phytoremediation purposes for various pollutants.…”
Section: Bioconcentration Factor (Bcf) and Translocation Factor (Tf) supporting
confidence: 66%
“…Canatto et al (2021) considered L. punctata as a hyperaccumulating species of arsenate after observing the tolerance indices relative to different levels of this contaminant. Ertekin et al (2015) also indicated the species for phytoremediation of water contaminated with hydrocarbons from petroleum.…”
Section: Resultsmentioning
confidence: 98%
“…The species has a fast growth rate and the capacity to develop in wastewater, thus being a candidate for the phytoremediation processes (Stegemeier et al, 2017). The literature indicates that L. punctata is a species with a great capacity to bioaccumulate arsenic, nickel, zinc, and uranium (Nie et al, 2017) and petroleum hydrocarbons (Ertekin et al, 2015). In this context, this study aimed to assess fluoride mitigation by the species L. punctata when submitted to different values of phosphate, nitrate, and pH.…”
Section: Introductionmentioning
confidence: 99%